Plasmonic Gold Nanocones in the Near‐Infrared for Quantum Nano‐Optics. Issue 22 (13th September 2017) - Flatae, Assegid Mengistu; Tantussi, Francesco; Messina, Gabriele C.; Mohammadi, Ahmad; De Angelis, Francesco; Agio, Mario
Abstract: Plasmonic gold nanocones offer outstanding possibilities to control light‐matter interaction at the nanoscale. For instance, they can be exploited to modify the photonic environment around a single emitter for tuning its quantum efficiency and radiative decay rate, as well as the angular distribution and polarization of the emitted photons. However, fabricating high quality nanostructures with the desired aspect ratio and tip radius of curvature is still challenging. Here, this study reports on the fabrication of high‐quality plasmonic gold nanocones based on electron beam‐induced deposition of an organometallic precursor on a substrate to define the structures, followed by sputtering deposition of a gold layer. The technique is versatile and has a very good spatial resolution for the fabrication of nanocones with dimensions in the 100 nm range and a small aspect ratio, while exhibiting a very sharp tip radius of curvature down to 6 nm. The nanocones are engineered to have resonances in the near‐infrared region, where absorption in gold is smaller. Using single‐nanoparticle spectroscopic techniques, this study characterizes their optical properties and measures the plasmon resonances, finding linewidths down to 50 nm. Abstract : High‐quality plasmonic nanocones are fabricated by focused electron beam‐induced deposition of platinum, followed by sputtering of a thin gold layer. Precise control over the geometrical parameters leads to reproducible nanocone tips with single‐digit radius of curvature. The plasmon resonance is tunable in the near‐infrared spectral region, exhibiting large radiation efficiency and longer plasmon dephasing times.